Pergeseran Paradigma Hukum - K. A Bukhori (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2018)
Positivists may declare that metaphysics (transcendental) is dead, but now it is logical positivism that first died. It is remarkable that the era of Muslim, Jewish and Christian theist thinkers is now again engaged in a vast exploration of the idea of